Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper on Estonia examines impact of assessing competitiveness and exposure to shocks integrating global value chains (GVCs). This paper strengthens the analytical underpinnings of competitiveness assessments and exposure to shocks by incorporating GVCs. Standard real effective exchange rates (REER) indexes assume trade is only in final goods. However, like most European economies, Estonia is highly integrated into GVCs. This implies that assessments of competitiveness should consider trade in value added. Based on a structural model, the paper assesses competitiveness and exposure to trade shocks accounting for the GVC participation in Estonia. The analysis using a REER index considering the GVC architecture suggests potential competitiveness problems in Estonia. The paper also estimates the impact of overvaluation (and appreciation) of the GVC related REER measure on value added export and real GDP growth and finds observable effects. Further, trade tension induced tariff hikes may have important costs for value added produced in Estonia.